Algorithm for the analysis of deformations and stresses due to torsion in a metal beam from LIDAR data. Issue 7 (28th December 2015) - Cabaleiro, M.; Riveiro, B.; Arias, P.; Caamaño, J. C.
Summary: An interesting field for application of LIDAR technology is structural health monitoring, especially in the study of deformation and stress in the beams. In the beams, it is not only the deformation due to bending that is an issue of control but it is also important to check the deformation due to torsion, particularly in open cross sections such as I, U, L, which have a very low torsional strength. This paper presents a new algorithm for obtaining, automatically and separately, the deformations in a beam subjected to torsional and bending loading, respectively, from LIDAR data. With the values of the deformation found by the new developed algorithm, the shear stresses are obtained. The methodology presented in this paper has been tested with a real beam in a laboratory under different load situations. The results obtained from the algorithm were compared not only with measurements by direct methods but also with results obtained by FEM simulation of the 3D model of the beam. The results found by the new algorithm compare with the other methods; therefore, this verifies the validity of the method for applications of structural health monitoring of metal structures. Copyright © 2015 John Wiley & Sons, Ltd.